Phenotypic reversion in fas mutants of Arabidopsis thaliana by reintroduction of FAS genes: variable recovery of telomeres with major spatial rearrangements and transcriptional reprogramming of 45S rDNA genes. (18th October 2016) - Pavlištová, Veronika; Dvořáčková, Martina; Jež, Michal; Mozgová, Iva; Mokroš, Petr; Fajkus, Jiří
Summary: Arabidopsis thaliana mutants dysfunctional in the evolutionarily conserved protein complex chromatin assembly factor‐1 (CAF‐1), which deposits the canonical histone H3 variant H3.1 during DNA synthesis‐dependent chromatin assembly, display complex phenotypic changes including meristem and growth alterations, sensitivity to DNA‐damaging agents, and reduced fertility. We reported previously that mutants in the FAS1 subunit of CAF‐1 progressively lose telomere and 45S rDNA repeats. Here we show that multiple aspects of the fas phenotype are recovered immediately on expression of a reintroduced FAS1 allele, and are clearly independent of the recovery of rDNA copy‐numbers and telomeres. In reverted lines, 45S rDNA genes are recovered to diverse levels with a strikingly different representation of their variants, and the typical association of nucleolar organizing region 4 with the nucleolus is perturbed. One of 45S rDNA variants (VAR1), which is silenced in wild‐type (WT) plants without mutation history (Col‐0 WT), dominates the expression pattern, whereas VAR2 is dominant in Col‐0 WT plants. We propose an explanation for the variability of telomere and 45S rDNA repeats associated with CAF‐1 function, suggesting that the differences in nuclear partitioning and expression of the rDNA variants in fas mutants and their revertants provide a useful experimental system to study genetic and epigenetic factors in gene dosage compensation. Significance Statement: Arabidopsis thaliana plants dysfunctional in Chromatin Assembly Factor‐1 (CAF‐1) ( FASCIATA or fas mutants) show complex phenotype together with progressive and specific loss of telomere repeats and 45S ribosomal RNA genes (rDNA). Restoration of CAF‐1 results in partial or full recovery of telomeres and rDNA and WT phenotype restoration which is independent of these changes. Moreover, revertants show major spatial rearrangements and transcriptional reprogramming of rDNA offering a unique experimental model to address rDNA maintenance and transcriptional control.